Capitalism in the age of globalization : the management of contemporary society - Amin, Samir; Foster, John Bellamy (Zed Books, 2014)
Samir Amin remains one of the world's most influential thinkers about the changing nature of North-South relations in the development of contemporary capitalism. In this highly prescient book, originally published in 1997, he provides a powerful analysis of the new unilateral capitalist era following the collapse of the Soviet model, and the apparent triumph of the market and globalization